Vibration Signal Analysis Based on Spherical Error Compensation - Wei, Shan (Frontiers in Bioengineering and Biotechnology, 2022)
Vibration sieve is an essential production link in mineral industry. Its main equipment is vibrating screen. Vibrating screen has been widely used in the ore industry, but there are also great problems in the use of vibrating screen. The working principle of vibrating screen works due to the vibration excitation force generated by vibration. This paper studies the motion trajectory of vibrating screen by taking the vibrating screen with line motion trajectory as the research object. By using the program designed by VC + + software to process the collected data, then simulate and fit, and finally calculate the trajectory of the moving vibrating screen. Judge the vibration amplitude according to the motion track, judge the working condition and efficiency of the vibrating screen according to the motion track and amplitude, and test the impact of the vibrating screen on the surrounding environment.